The role of actin-binding proteins in the control of endothelial barrier integrity - García-Ponce, Alexander; Citalán-Madrid, Alí Francisco; Velázquez-Avila, Martha; Vargas-Robles, Hilda; Schnoor, Michael (Thrombosis and Haemostasis, 2015)
The endothelial barrier of the vasculature is of utmost importance for separating the blood stream from underlying tissues. This barrier is formed by tight and adherens junctions (TJ and AJ) that form intercellular endothelial contacts. TJ and AJ are integral membrane structures that are connected to the actin cytoskeleton via various adaptor molecules. Consequently, the actin cytoskeleton plays a crucial role in regulating the stability of endothelial cell contacts and vascular permeability. While a circumferential cortical actin ring stabilises junctions, the formation of contractile stress fibres, e. g. under inflammatory conditions, can contribute to junction destabilisation. However, the role of actin-binding proteins (ABP) in the control of vascular permeability has long been underestimated. Naturally, ABP regulate permeability via regulation of actin remodelling but some actin-binding molecules can also act independently of actin and control vascular permeability via various signalling mechanisms such as activation of small GTPases. Several studies have recently been published highlighting the importance of actin-binding molecules such as cortactin, ezrin/ radixin/moesin, Arp2/3, VASP or WASP for the control of vascular permeability by various mechanisms. These proteins have been described to regulate vascular permeability under various pathophysiological conditions and are thus of clinical relevance as targets for the development of treatment strategies for disorders that are characterised by vascular hyperpermeability such as sepsis. This review highlights recent advances in determining the role of ABP in the control of endothelial cell contacts and vascular permeability.
Keywords: Actin cytoskeleton; cell-cell interactions; endothelial cells; GTPases; inflammation; vascular permeability